Production of protease by Pseudomonas aeruginosa and Staphylococcus aureus isolated from abattoir environment - CO, Akujobi; NN, Odu; SI, Okorondu; GN, Ike (Journal of Research in Biology, 2012)
The study investigated the optimum conditions of temperature, pH, inoculum size and time of incubation on bacterial protease production. Protease producing bacterial species were isolated from abattoir soil and identified as Pseudomonas aeruginosa and Staphylococcus aureus. The optimum conditions observed for protease production was 37 oC at pH 9, with 2 % inoculum in the medium for 24 h of incubation. Pseudomonas aeruginosa had higher protease activities at optimum temperature and pH than Staphylococcus aureus while S. aureus had higher protease activities at optimum incubation time of 24 h and inoculum concentration of 2 %. The study gave evidence that these bacterial isolates could be potentially applied in biotechnological processes